Perlindungan Hukum Bagi Konsumen Dalam Transaksi Jual Beli Rumah Serta Hak Dan Kewajiban Developer - Rida Ardiana; Salsabila Alya Putri; Indah Febriyana; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
Legal protection for consumers in a buying and selling transaction, especially in buying and selling houses, has become increasingly important judging from the increasing property value at this time. The transaction of buying and selling houses involves a very important interest in consumers, including the rights and obligations of developers. This journal will discuss regulations that apply to real practice in the field, this journal is expected to provide comprehensive information and overview of existing legal protection. This journal will discuss in more depth various relevant legal aspects regarding protection for consumers who make house buying and selling transactions, not only that this journal will discuss the rights and obligations of a developer regarding the process of buying and selling houses